Impact of marine algae extract and balanced fertilizer(NPK) on Hibicsus sabdariffa L. growth, quotient and vitamin C content - AL-Ajili, Hanan Ali Hussein; Almosawy , Ahmed Najm (Journal of Kerbala for Agricultural Sciences, 2024)
A field experiment was conducted in one of the experimental fields affiliated to Ibn Al-Bitar Vocational Preparatory School located in Al-Hussainiyah District - Karbala Governorate during the 2023 agricultural season with the aim of studying the impact of adding different concentrations of marine algae extract, balanced fertilizer in the growth qualities, yield and vitamin C in the roselle plant. The experiment was carried out according to a randomized complete block design (RCBD) with factorial arrangment and three replications. The experiment included two factors. The first factor included spraying with marine algae extract in concentrations ( 0, 0.25, 0.5 and 0.75 ml L-1) . The second factor included spraying with balanced fertilizer (NPK) in concentrations (0, 2.5 and 5 ml L-1). The results showed that spraying with marine algae extract (0.75 ml L-1) has a significant superiority in the vegetative growth qualities and vitamin C content of the roselle plant compared to other agile agreements, and the spraying with balanced fertilizer at a concentration of (5 ml L-1) It significantly excelled in all study indicators. The interaction between the two study factors, The spray treatment superiority (0.75 ml L-1) of algae extract with the of balanced fertilizer (5 ml L-1), and gave the highest averages for all the studied qualities., giving the highest Means for all the studied qualities.